(untitled) (American International Journal of Education and Linguistics Research, 2018)
According to the changes in parents attitude towards the school are following different types of syllabuses, namely, State board, CBSE, Matriculation and Delhi board. They are also following various types of teaching techniques using overhead projector, group discussion charts, models etc., They are more popularly used teaching aids in institution following, matriculation and CBSE syllabus. This helps the students to shine in their subjects. The teaching methods and curriculum are getting more attention in private schools. The parents are preferring matriculation and CBSE syllabi which have more subjects and more practical with computer knowledge. The objectives of the present study is to know the perception of parents towards matriculation schools. It is found that there is no significant association between socio economic profile of the respondents and their level of perception towards matriculation schools.